Architectural Structure - Almeida Bernardo, Luís Filipe (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The Special Issue, "Architectural Structure," aims to gather general advances in human-made constructions which simultaneously are driven by aesthetic and structural engineering considerations. This Special Issue brings together twelve contributions covering the following topics: analysis of architectural typologies; the study of the mechanical performance of structural materials, structural systems and components; and the proposal of techniques to evaluate the mechanical performance in existing structures and new construction techniques.